2019
DOI: 10.1302/2058-5241.4.180099
|View full text |Cite
|
Sign up to set email alerts
|

Why does radial head arthroplasty fail today? A systematic review of recent literature

Abstract: Since the introduction of the radial head prosthesis (RHP) in 1941, many designs have been introduced. It is not clear whether prosthesis design parameters are related to early failure. The aim of this systematic review is to report on failure modes and to explore the association between implant design and early failure. A search was conducted to identify studies reporting on failed primary RHP. The results are clustered per type of RHP based on: material, fixation technique, modularity, and polarity. Chi-squa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 47 publications
0
26
0
Order By: Relevance
“…However, as clinical studies found, prosthetic replacement of the radial head comes with complications, with loosening being the most common one together with overstuffing [26]. The most commonly observed loosening is aseptic loosening [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, as clinical studies found, prosthetic replacement of the radial head comes with complications, with loosening being the most common one together with overstuffing [26]. The most commonly observed loosening is aseptic loosening [9].…”
Section: Discussionmentioning
confidence: 99%
“…In general, the implants can be differentiated into monopolar and bipolar implants. While the bipolar implants allow movement of the head component, the monopolar ones rely on a simpler construct with rigid fixation of the head to the respective neck or shaft [8,9]. Although the clinical outcomes after radial head arthroplasty are reliable, specific complications have been reported [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reported complications have consisted of nerve palsy, instability, stiffness, persistent pain, (superficial) infection, complex regional pain syndrome (CRPS) and symptomatic hardware. 10 Revision surgery was performed in a significant group of patients that experienced complications (23%) following primary RHA. A systematic review on RHA by our study group showed that, on average, 8% of radial head prosthesis had been revised early, within four years of follow-up.…”
Section: Radial Head Arthroplastymentioning
confidence: 99%
“…All recommendations are based on a critical appraisal of the literature on (revision) RHA that was recently systematically reviewed by our study group. 7 , 10 See also Table 1 . That same literature search was the basis for the current article.…”
Section: Introductionmentioning
confidence: 99%